The Phylogeny and Biogeographic History of Ashes (Fraxinus, Oleaceae) Highlight the Roles of Migration and Vicariance in the Diversification of Temperate Trees - Hinsinger, Damien Daniel (Public Library of Science, 2013)
The cosmopolitan genus Fraxinus, which comprises about 40 species of temperate trees and shrubs occupying various habitats in the Northern Hemisphere, represents a useful model to study speciation in long-lived angiosperms. We used nuclear external transcribed spacers (nETS), phantastica gene sequences, and two chloroplast loci (trnH-psbA and rpl32-trnL) in combination with previously published and newly obtained nITS sequences to produce a time-calibrated multi-locus phylogeny of the genus. We then inferred the biogeographic history and evolution of floral morphology. An early dispersal event could be inferred from North America to Asia during the Oligocene, leading to the diversification of the section Melioides sensus lato. Another intercontinental dispersal originating from the Eurasian section of Fraxinus could be dated from the Miocene and resulted in the speciation of F. nigra in North America. In addition, vicariance was inferred to account for the distribution of the other Old World species (sections Sciadanthus, Fraxinus and Ornus). Geographic speciation likely involving dispersal and vicariance could also be inferred from the phylogenetic grouping of geographically close taxa. Molecular dating suggested that the initial divergence of the taxonomical sections occurred during the middle and late Eocene and Oligocene periods, whereas diversification within sections occurred mostly during the late Oligocene and Miocene, which is consistent with the climate warming and accompanying large distributional changes observed during these periods. These various results underline the importance of dispersal and vicariance in promoting geographic speciation and diversification in Fraxinus. Similarities in life history, reproductive and demographic attributes as well as geographical distribution patterns suggest that many other temperate trees should exhibit similar speciation patterns. On the other hand, the observed parallel evolution and reversions in floral morphology would imply a major influence of environmental pressure. The phylogeny obtained and its biogeographical implications should facilitate future studies on the evolution of complex adaptive characters, such as habitat preference, and their possible roles in promoting divergent evolution in trees.